2017
DOI: 10.1177/1045389x17730912
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological properties and polishing characteristics of silica-coated carbonyl iron magnetorheological fluid

Abstract: While magnetorheological fluids can be used for ultra-precise polishing, for example, of advanced optical components, oxidation of metallic particles in water-based magnetorheological fluids causes irregular polishing behavior. In this study, carbonyl iron microspheres were initially coated with silica to prevent oxidation and were used to polish BK7 glass. In addition, their rheological and sedimentation characterizations were investigated. Material removal and surface roughness were analyzed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…Hence, the higher the content of Fe3O4 and the greater the interaction, leading to an effective decrease in the swelling ability. These observations are consistent with those of other researchers [40]. In summary, these water swelling experiments showed that the introduction of nanoparticles Fe3O4 into the PAAM matrix affects its swelling behavior.…”
Section: Swelling Behavior Of Magnetic Hydrogels With Fe 3 Osupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the higher the content of Fe3O4 and the greater the interaction, leading to an effective decrease in the swelling ability. These observations are consistent with those of other researchers [40]. In summary, these water swelling experiments showed that the introduction of nanoparticles Fe3O4 into the PAAM matrix affects its swelling behavior.…”
Section: Swelling Behavior Of Magnetic Hydrogels With Fe 3 Osupporting
confidence: 93%
“…Methacrylic acid (MAA, 99%), (VTMOS 98%), and ethanol (98.8%) were purchased for surface pretreatment of CI. We pre-treated the surface of CI by coating with silica to prevent their oxidation before preparing the magnetic hydrogels [40]. First, the CI, ethanol solution, and MAA were added to a beaker and then treated by the ultrasonic dispersion method for 30 min at 25 • C. Next, VTMOS was poured into the mixture with full mechanical stirring at 400 rpm for 20 min.…”
Section: Raw Materialsmentioning
confidence: 99%
“…This superior surface property of the coated CIP exhibited similar pattern outcomes discovered by the same research team of Lee et al (2017) [ 54 ], but this time, the CIP were coated with a biopolymer, xanthan gum. On the other hand, a study by Hong et al (2018) [ 58 ] also showed the decrease in surface roughness of BK7 glass when the CIP used in their MR polishing fluid was coated with silica, especially when an abrasive was introduced into the MRF. These end results can definitely be utilized in ultra-precision applications in optics and micro parts industries.…”
Section: Particle Coating In Mr Materialsmentioning
confidence: 99%
“…The effects of corrosion in MR materials have also been discussed in detail by Plachy et al (2018) [ 17 ] and Burhannuddin et al (2020) [ 63 ] in separate works around MRF and MRE, respectively. Furthermore, rougher surfaces of oxidized particles may lead to irregular polishing performance as well as reducing the lifetime of the vessels that contain the MR materials, because rougher surfaces can cause unnecessary friction between the particles and the wall of the vessels after a long operational period [ 57 , 58 , 64 ]. These problems can be minimized by developing coatings that act as a barrier to the oxidation species.…”
Section: Particle Coating In Mr Materialsmentioning
confidence: 99%
“…We followed a similar procedure as described in reference (Hong et al, 2018) to treat the surface of CIPs before they are magnetically aligned within hydrogels. Ten grams of CIPs and 1.2 g of MAA were added to the ethanol solution and then underwent ultrasonic dispersion at room temperature for 30 min.…”
Section: Surface Pre-treatment Of Carbonyl Iron Particlesmentioning
confidence: 99%